2021
DOI: 10.1001/jamaoncol.2021.1364
|View full text |Cite
|
Sign up to set email alerts
|

Association of Screening Lower Endoscopy With Colorectal Cancer Incidence and Mortality in Adults Older Than 75 Years

Abstract: IMPORTANCEEvidence indicates that screening for colorectal cancer (CRC) beginning at 50 years of age can detect early-stage CRC and premalignant neoplasms (eg, adenomas) and thus prevent CRC-related mortality. At present, the US Preventive Services Task Force recommends continuing CRC screening until 75 years of age and individualized decision-making for adults older than 75 years, while accounting for a patient's overall health and screening history. However, scant data exist to support these recommendations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…Individuals with prior negative screening history may have reduced risk, whereas unscreened individuals are at a higher risk for CRC than adequately screened patients. Screening should be initiated for those who have never been screened, even after the age of 75 years for individuals without significant comorbidities[ 43 ].…”
Section: Risk Factors For Developing Crcmentioning
confidence: 99%
“…Individuals with prior negative screening history may have reduced risk, whereas unscreened individuals are at a higher risk for CRC than adequately screened patients. Screening should be initiated for those who have never been screened, even after the age of 75 years for individuals without significant comorbidities[ 43 ].…”
Section: Risk Factors For Developing Crcmentioning
confidence: 99%
“…This result is consistent with the current ACG and USPSTF clinical guidelines that recommend against routine cancer screening for colorectal cancer in adults aged 76 and older ( Davidson et al, 2021 ). However, clinical studies showed that people who had colorectal cancer screening after age 75 had a lower risk of colorectal cancer and a lower risk of death from colorectal cancer ( Ma et al, 2021 ). Due to this reason, individuals older than 75 years of age may be more likely to get FOBT, which is a noninvasive test and can be performed at home.…”
Section: Discussionmentioning
confidence: 99%
“…CRC is usually asymptomatic in the early stages. Symptoms appear in the advanced stages of cancer ( Ma et al., 2021 ). Hematochezia is a warning sign for CRC, but colon bleeding is sometimes very mild and cannot be detected.…”
Section: Discussionmentioning
confidence: 99%